Forbes Disease: A Case Report - Ara, Rowsan; Alam, Md Zahid; Ahmed, Sharmin (BIRDEM Medical Journal, 2017)
Glycogen storage disease (GSD) type 3 (Forbes disease) is an autosomal recessive inborn error of metabolism caused by loss of function mutations of the glycogen debranching enzyme (Amylo- 1, 6-glucosidase [AGL]) and (oligo-1,4-1,4-glucanotransferase) gene, which is located at chromosome band 1p21.2. GSD 3 is characterized by the storage of structurally abnormal glycogen, termed limit dextrin, in both skeletal and cardiac muscle and/or liver, with great variability in resultant organ dysfunction. Here we describe a 16 yearold boy diagnosed as a case of epilepsy at the ageof 8. He presented to us with inadequately controlled seizure, profound proximal weakness, hepatosplenomegaly and right-sided ballotable kidney. The final diagnosis of glycogen storage disease was made by clinical features, lab reports and liver histopathology that revealed PAS positive diastase labile glycogen accumulation within swollen hepatocytes. The particular interest of this paper is to present a case of glycogen storage disease and demonstrate the difference between that entity and other storage diseases. Birdem Med J 2017; 7(1): 60-63